The Contribution of Nintendo Wii® in children’s motricity - Gil, Henrique (2019)
The increasingly visible sedentarism in the children of our current society is a problem that has been worrying the Childhood Educators. Taking into account the advancement of technology and the fact that children in today's activity rooms are considered as Digital Natives, we intend to introduce the Nintendo Wii® into the motor activities developed by children in order to verify their contribution to children's motor skills. To this end, the objectives of this study focused on the promotion of digital resources in activities related to motor expression; the analysis of the effect of the practice of motor activities performed with Nintendo Wii® and the identification of changes in children's motor development, namely in the analyzed variables, balance, laterality, body notion and global praxia, resulting from practice in the environment virtual. The present investigation was developed in the Supervised Practice in Pre-School Education, in a group of children between the ages of 4 and 5 years. In this investigation the qualitative and quantitative paradigm was combined. A mixed qualitative approach was also developed, combining action research and exploratory case study, due to the uniqueness of the study. For the collection of data, several instruments and techniques were used: participant observation, field notes, audiovisual media, BPM, semistructured interview and questionnaire surveys. The implementation was developed in seven sessions, in which the children of the experimental group used the Nintendo Wii® and its accessories (Wii Remote and Balance Board). After the due analysis of all the collected data, we can conclude that the Nintendo Wii® contributes significantly in the children's motricity, that is, in the improvement of motor skills. It is noteworthy that the accomplishment of motor activities with the Nintendo Wii® generated in the children spontaneous collaborative spirit; healthy competition, because what mattered was the accomplishment of motor activities and not exactly the gain of points, and the punctuation emerged as a motivating element in terms of people, giving rise to greater feelings of selfesteem.